There is an error in the process of completing the square on the left hand side while going from line 3 to line 4, since

`b^2+1/2b+(1/2)^2!=(b+1/2)^2.`

A correct solution starting at line 3 would be

`b^2+1/2b+(1/4)^2=3+(1/4)^2`

`(b+1/4)^2=3+1/16`

`b+1/4=+-sqrt(49/16)`

`b=-1/4+-7/4`.

This gives the two solutions `b=3/2` and `b=-2.`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now